Hypo-high density lipoproteinemia is a predictor for recurrent stroke during the long-term follow-up after revascularization in adult moyamoya disease - Yu, Xiaofan; Ge, Peicong; Zhai, Yuanren; Wang, Rong; Zhang, Yan; Zhang, Dong (Frontiers in Neurology, 2022)
Objective: Previous studies have reported that hypo-high density lipoproteinemia (HHDL) was an independent risk factor for cerebrovascular event. However, the risk of HHDL for stroke recurrence in moyamoya disease (MMD) during long-term follow-up after revascularization remains poorly understood. We aim to investigate the association between HHDL and stroke recurrence of adult patients with MMD. Methods: A total of 138 adult patients with MMD were prospectively recruited from July 1 to December 31, 2019. After excluding 15 patients who did not meet the inclusion criteria, all 123 patients were enrolled. Participants were grouped according to stroke recurrence and HHDL presentation, respectively. Clinical data and laboratory examinations were compared by statistical analysis. Kaplan-Meier survival analysis was conducted to compare the stroke-free survival rates between participants with HHDL and those without. Univariate and multivariate logistic regression analysis were performed to identify independent factors of the neurological status. Univariate and multivariate Cox regression analysis were conducted to identify the predictors for recurrent stroke. Results: Participants with recurrent stroke group showed a lower level of high density lipoprotein (HDL) (p = 0.030). More participants in the recurrent stroke group had HHDL (p = 0.045). What’s more, there was statistical significance in the Kaplan-Meier curve of stroke incidence between the normal HDL group and the HHDL group (log-rank test, p = 0.034). Univariate logistic analysis results showed that HHDL (OR 0.916, 95% CI 0.237-3.543; p = 0.899) and HDL (OR 0.729, 95% CI 0.094-5.648; p = 0.763) were not predictive factors for the neurological status. In the multivariate Cox regression analysis, diabetes (HR 4.195, 95% CI 1.041-16.899; p = 0.044), HDL (HR 0.061, 95% CI 0.006-0.626; p = 0.019), HHDL (HR 3.341, 95% CI 1.110-10.051; p = 0.032) were independent risk factors for recurrent stroke. Conclusions: HHDL might be a predictor or potential therapeutic target for recurrent stroke during the long-term follow-up after revascularization in adult patients with MMD.